Respuesta :

y=-1.4
all you had to do was the elimination method
Yexs
[tex]Hi \\ \\ \begin{cases}4x-y=2~~----\ \textgreater \ (I) \\ 2x+9y=- 12~--\ \textgreater \ (II)\end{cases} \\ \\ \underline{Resolution ~} \\ \\~~~~~~4x-y=2 \\ =\ \textgreater \ \boxed{y=4x-2}~~--\ \textgreater \ \textcircled{1} \\ \\ \mathbb{tttttttttttttttttttttttttttttttttttt} \\\textcircled{1}~in (II) \\ \\2x+9\underbrace{y}_{4x-2}=-12 \\ \\ 2x+9(4x-2)=-12 \\ \\ 2x+36x-18=-12 \\ \\ \boxed{\boxed{x=0,16}} \\ \\ \mathbb{tttttttttttttttttttttttttttttttttttt} \\ =\ \textgreater \ y=4x-2 \\ ~~~~~~y=4(0,16)-2 \\ ~~~~~~\boxed{\boxed{y=-1,36}}\\ \\ \\ .[/tex]

[tex]\therefore~(x;y)=(0,16; -1,36)[/tex]
ACCESS MORE